Positive solutions for a coupled system of nonlinear fractional differential equations. (21st May 2014) - Zhang, Keyu; Xu, Jiafa; O'Regan, Donal
Abstract: Using the Krasnoselskii–Zabreiko fixed point theorem, we establish two existence theorems for positive solutions of a coupled system of nonlinear fractional differential equations. Power functions and nonnegative matrices are used to characterize coupling behavior of our nonlinearities, so nonlinearities may grow differently; in fact, one may grow superlinearly, and the other may grow sublinearly. Copyright © 2014 John Wiley & Sons, Ltd.